Tensodynamometric and spatial-temporal characteristics of defensive moving reaction of a law-enforcement officer in response to an attack of an armed enemy - RADZIEVSKIY, R. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to examine the tensodynamometric and spatial-temporal characteristics of a law-enforcement officer’s defensive movements in response to the moving attacking actions of an offender. To identify the efficient ways how to counter the attack of the enemy armed with the firearms. Material: It was surveyed 62 employees of practical units of law enforcement authorities. It was experimented with 15 cadets of Kyiv National Academy of Internal Affairs and 15 employees of Department of the State Guard of Ukraine. Results: As a result it was found out that the participants adapted to true-life armed conflicts with the offender. On the basis of the broadened knowledge about the outer indicators of the menace and spatial-temporal characteristics of the movements of the armed enemy it was created the moving behavior of the law-enforcement officer. Conclusions: In case of an armed enemy’s attack it is recommended to carry out the defensive action lunging aside with the optimum cooperation of supporting reactions and action in response, shooting on account of “muscle memory” of the angle of the pointed gun and the projection of the straight line in accordance with the gun tube, the target and the spatial characteristics.